PERBANDINGAN KUALITAS KULIT SAPI WET BLUE DENGAN MASA PENYIMPANAN BERBEDA - Laili Rachmawati; Tria Novianti; Maria Sri Wiyanti (Politeknik ATK Yogyakarta, 2018)
Raw materials storage is important in the leather tanning industry. The obstacle faced by PT Usaha Loka East Java was the problem of decreasing the quality of hide wet blue with different storage periods, so this study is to examine the difference quality of hide wet blue≤ 12 months and ≥ 24 months of storage. Physical testing was carried out at Balai Besar Kulit Karet dan Plastik (BBKKP) Yogyakarta. The results of testing the quality of hide wet blue with a storage period of ≤12 months included moisture content, tensile strength, area of defect and softness respectively were 34.2 ± 0.47%; 23.73 ± 0.32 N / mm2; 1.7 ± 0.85%; and 3.8 ± 0.37 while the results of tests on the quality of the wet cow leather with a storage period of ≥24 months were 5.8 ± 0.40%, respectively; 19.62 ± 0.28 N / mm2; 3.0 ± 0.57; and 2.2 ± 0.66. The decrease of hide wet blue quality with ≥ 24 months storage period was more than ≤ 12 months (p < 0,05).